The sense and nonsense of antipsychotic combinations: a model for dopamine D2/3 receptor occupancy - Spangemacher, Moritz; Schmitz, Christian N.; Cumming, Paul; Färber, Luca V.; Hart, Xenia Marlene; Uchida, Hiroyuki; Gründer, Gerhard (Translational Psychiatry, 2025)
Approximately 20-30% of patients treated for schizophrenia concomitantly take two or more antipsychotic substances, despite the limited evidence that antipsychotic combination treatment is superior to monotherapy. Positron emission tomography (PET) studies can reveal the relationship between plasma levels of an antipsychotic medication and occupancy at striatal dopamine D2/3 receptors (D2R), but there is scant consideration in the literature of the net occupancy obtained with antipsychotic combination treatment. In this report, we introduce a novel model for predicting net D2R occupancy in antipsychotic polypharmacy (APP); taking as illustrative examples five commonly prescribed antipsychotic medications. In an extension of the law of mass action for predicting receptor occupancy from the plasma concentration of a single psychopharmacological agent, we test a model for inferring the net striatal D2R occupancy in APP from the individual Michaelis-Menten kinetics of two (or more) antipsychotic medications. Based on literature PET findings for striatal D2R occupancy in monotherapy, our model predicts that widely used antipsychotic medication combinations may exceed the optimal therapeutic window of 65-80% occupancy. Our extended model accurately predicted occupancy for the only APP combination documented by PET. Present results call for caution in the design of antipsychotic medication combination therapy, aiming to avoid excessive occupancy by adjusting drug concentrations and doses.
Im Titelzusatz sind die Zahlen 2 und 3 bei "dopamine D2/3" tiefgestellt
Gesehen am 18.12.2025